Traversing by Smartphones and Assessing the Accuracy of their Results in Lengths and Area - Mahdi, Hussein Alwan; Kadhim, Moowafaq Jawad (Iraqi Journal of Science, 2025)
Tracing is an essential process in geomatics (i.e., surveying) for different applications. It involves determining the positions of points from different measurements utilizing suitable techniques. Since the smartphone is a modern technology that can determine positions, assessing their results in traversing is necessary. For this purpose, the positions of 16 points in a closed traverse were collected with six different sets of measurements (five sets with smartphone devices and a standard set with traditional techniques). The smartphone devices are dual-frequency Samsung S22, and the other four are single-frequency, consisting of the iPhone 11, Xiaomi Note 8, the iPhone XS max, and the iPhone XS with Android application. The derived distances and computed area from each device were compared with the adjusted results of a standard set measured with theodolite and steel tape. The Root Mean Square Error (RMSE) of positioning with a dual-frequency device was found to be 0.700 m and 1.182 m for easting and northing, respectively, which is better than the positioning with single-frequency devices. The achieved RMSE in the extracted distance was 1.288m with dual frequency compared to 1.333 to 2.179m with other single-frequency devices. The standard computed area of the traverse was 47,824.54 m2, while it was 47,866.95 m2 for a dual-frequency device and 47,758.40 m2 to 47,165.64 m2 for other devices. This means the least difference in the area, 42.41 m2, was achieved with the dual-frequency device. It was proven that the results of a dual-frequency smartphone are better than that of single-frequency devices.